2019
DOI: 10.1029/2019ja026678
|View full text |Cite
|
Sign up to set email alerts
|

Whole Atmosphere Climate Change: Dependence on Solar Activity

Abstract: We conducted global simulations of temperature change due to anthropogenic trace gas emissions, which extended from the surface, through the thermosphere and ionosphere, to the exobase. These simulations were done under solar maximum conditions, in order to compare the effect of the solar cycle on global change to previous work using solar minimum conditions. The Whole Atmosphere Community Climate Model‐eXtended was employed in this study. As in previous work, lower atmosphere warming, due to increasing anthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
63
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 55 publications
15
63
2
Order By: Relevance
“…This can therefore also push global mean trends to be more negative than they would be due to the increase in CO 2 concentration alone. This is true for the neutral temperature at 400 km as well and may help to explain why the trends in especially the neutral temperature and h m F 2 we found remained somewhat large compared to Solomon et al (2018, 2019) even after solar cycle influences were removed as much as possible.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This can therefore also push global mean trends to be more negative than they would be due to the increase in CO 2 concentration alone. This is true for the neutral temperature at 400 km as well and may help to explain why the trends in especially the neutral temperature and h m F 2 we found remained somewhat large compared to Solomon et al (2018, 2019) even after solar cycle influences were removed as much as possible.…”
Section: Discussionsupporting
confidence: 72%
“…field. This is the other key difference between our study and Solomon et al (2018and Solomon et al ( , 2019, who kept the Earth's magnetic field fixed. Since magnetic field changes and their effects on the upper atmosphere are location-dependent, it is appropriate to go beyond global mean quantities for this and examine the spatial variations in trends.…”
Section: Global Mean Trendsmentioning
confidence: 87%
See 1 more Smart Citation
“…Recent modeling studies by Solomon et al (2018) and Solomon et al (2019) found that the increase in CO 2 concentration between the 1972-1976 and 2001-2005 periods caused a decrease in global mean N m F 2 of 1.2% per decade. Changes in global mean TEC would probably be somewhat smaller than this, as the F 2 peak is the part of the ionosphere that shows the largest response to CO 2 changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the actual observation of climate change contains both effects in several different time scales. Modeling efforts have been made to separate these two mechanisms (e.g., Egorova et al 2018;Solomon et al 2019). Comparison of these modeling efforts with longterm observation becomes increasingly important to identify the mechanisms on solar forcing to climate change.…”
Section: Separation Of Anthropogenic Effect and Solar Variability Effectmentioning
confidence: 99%